Income inequality among the smallholder irrigation farmers: the case of Hamamavhaire and Ngondoma irrigation schemes in the Midlands province of Zimbabwe - Chivizhe, Joseph, B.; Mugabe, Francis T.; Kadigi, Reuben M.J. (Gujarat Journal of Extension Education, 2020)
Zimbabwe developed smallholder irrigated agriculture initially as a famine relief strategy and later towards alleviation of poverty, employment creation and cushioning the country’s semi arid periodic droughts since the beginning of the twentieth century. The study evaluated the effect of smallholder irrigated agriculture on income distribution. A multistage sampling technique was used to select the two study areas of Ngondoma and HamaMavhaire comprising 71and 56 sample respondents respectively. A researcher administered questionnaire for collection of cross-sectional data. HamaMavhaire results show negative disaggregated income (USD 335.38) for the bottom quintile with the top quintile earning 64.07% of total income. Ngondoma results show earnings of 2.94%, and 58.7% of the income earned by the bottom and top quintiles respectively. The finding shows a Gini coefficient of 0.624 for HamaMavhaire and 0.516 for Ngondoma indicating greater income inequality in HamaMavhaire. Disaggregation of total income using the coefficient of variation and the Gini coefficient shows crop income and transfers being consistently inequality reducing sources, while self employment was inequality increasing. Livestock and non-farm income behaved differently being inequality reducing sources under the Gini coefficient and inequality increasing under the Coefficient of variation. However literature recommends Coefficient of variation than Gini coefficient as more meaningful measure.